On the dip of sea horizon - Ogura, S. (The International Hydrographic Review, 2018)
The Dip of Sea Horizon, with reference to the difference of temperature of the air and the sea water, is discussed. Tables by various authorities are given, and observations made by Mr. A. Sone on board H. J. M. S. Mansyü in the area of the “Kurosio” near the south coasts of Japan in January and February of 1926 are discussed. These observations were compared with the Kohlschütter Brehmer's Table for the correction of the ,dip of sea horizon, and it was found that the difference sometimes amounts to 4', the mean of differences (tabular value — observed value)being - i ' .8 and o’ .o for high and low altitudes respectively.